Ellipsometry of polycrystalline iron electrodes in alkaline solutions containing chloride ions under different electrochemical conditions - Juanto, S. (1987)
The ellipsometric and voltammetric responses of iron in 0.04 M NaOH + xM NaCl (0 ⩽ x ⩽ 0.3) are investigated. Three main processes, barrier layer formation, outer layer formation and pitting corrosion which depend differently on the presence of NaCl can be distinguished. The first process becomes practically independent of NaCl concentration. Otherwise, under certain conditions NaCl increases the charge associated with the outer layer formation through pitting. The dependence of the latter on NaCl concentration is in agreement with data earlier reported in the literature. A relation among the three processes is discussed in terms of competitive anion adsorption on iron specimen and formation of redox couples within the hydrous oxide layer produced on iron.